A serious canker disease caused by Immersiporthe knoxdaviesiana gen. et sp. nov. (Cryphonectriaceae) on native Rapanea melanophloeos in South Africa. (21st August 2012) - Chen, S. F.; Wingfield, M. J.; Roets, F.; Roux, J.
<x xml:space="preserve">Abstract</x> Recent disease surveys in the Western Cape province of South Africa have revealed a previously unknown and serious stem canker disease on native Rapanea melanophloeos (Myrsinaceae, Ericales) trees. Cankers commonly result in the death of branches or entire stems. Fruiting structures typical of fungi in the Cryphonectriaceae were observed on the surfaces of cankers. In this study, the fungus was identified and its pathogenicity to R. melanophloeos was tested. Multigene phylogenetic analyses based on DNA sequences of the partial LSU gene, ITS region of the nuclear ribosomal DNA gene and two regions of the β‐tubulin (BT) gene, showed that the fungus represents a formerly undescribed genus and species in the Cryphonectriaceae. The fungus was also morphologically distinct from other genera in this family. Inoculation trials showed that the fungus described here as Immersiporthe knoxdaviesiana gen. et sp. nov. is an aggressive pathogen of R. melanophloeos trees.